Development of the organic production in Ukraine: problems and perspectives - Fedchyshyn, Dmytro; Ignatenko, Iryna; Danilik , Daria; Chyryk, Alyona (Revista de Ciências Agroveterinárias, 2022)
This review article examines the legal support and proper state support of organic production in Ukraine, substantiation of the potential and obstacles to the development of organic production, as well as proposals for improving the current legislation. This review also analyzes the modern market of organic products, which, in terms of growing consumer demand for environmentally friendly and safe for human health, is very perspective for Ukraine. The increase in the area of agricultural land allocated for organic production, the number of domestic organic operators, and the ever-increasing volume of exports of organic products to other countries indicate a steady trend of growth and further development of this market. However, it is noted that the need to form the infrastructure of the organic products market still remains important. In addition, the problem of improving the system of standardization and certification of production, processing, storage and transportation of organic products, as well as the introduction of an effective control system over the sale of organic raw materials, are the main challenges to be solved.